PENGARUH PENERAPAN METODE SOSIODRAMA TERHADAP KEMAMPUAN BERBICARA ANAK USIA 4-5 TAHUN DI TAMAN KANAK-KANAK SANDHY PUTRA TELKOM KECAMATAN MARPOYAN DAMAI PEKANBARU - Sukmawati Sukmawati; Daviq Chairilsyah; Hukmi Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: This study aims to determine the effect of applying the method of the ability to speak sociodramas children aged 4-5 years in kindergarten Sandhy Putra Telkom Pekanbaru. The population and sample of this research is the age of 4-5 years amounted to 15 children. Data collection techniques were used that observation. Technical Data analysis was performed using t-test statistics with SPSS for Windows Ver 17. Statistical techniques t-test was used to test the difference before and after the action. Criteria for decision making in hypothesis testing based on the probability value of t statistic (sig.t) obtained based on the level of significance (α) = 0.05. When the value of p <0.05 means that there is a positive and significant influence. Pre test results obtained from a total value of 141 and a value of 44.76%. After carrying out the experiment with the use of Implementation Method Sociodramas, then carry out the next stage in the form of charging sheet Post test observations of the Children's Speech. From the results of the test after the Post obtained a total value of 264 and an average of 83.81%. So the value of Pre test Post test 44.76- 83.81 = value amounted to 39.05%. Testing using t test and it is known that a significant effect, with a value of 7.78 t, due to the significant level of 5% = 2.14 and at significant level of 1% = 2.98, meaning <of the value of 7.78 so it can be said to be significant, thus the increase.Key words: speech, application methods sociodrama